The relationship between smoking and Urokinase gene 3’-UTR T/C expression on occurrence of bladder cancer - Zainab Nizar Jawad 1, Kamal Abdul Rasool 1, Weaam Awad 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bladder cancer (CA Bladder) is the malignancy that affects the lining of the bladder (which is the most common types of urinary epithelial cancers that associated with the most invasive types of cancers and has the highest incidence of recurrence and infections). This study was designed to investigate the role of cigarette smoking on expression of urokinase gene that has a prominent role in the incidence of CA bladder. The samples were collected from 90 patients after being clinically diagnosed by the specialist surgeon of Imam Hussein Center for Cancer Diseases, Holy Kerbala, Iraq who were heavily smokers (more than one pocket/day). These patients were compared to 90 non-smoker patients with CA bladder and 90 persons who apparently healthy individuals as a control groups, DNA was extracted from all blood samples. The level of gene expression was correlated with cycle threshold value calculated by using real time PCR. The results showed significant association between smoking and occurrence of CA bladder (by increased expression of urokinase 3’-UTR T/C gene) in comparison to both control and non-smoker patients groups